Homework: Occupational Handbook - McGuire, Gail (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The Sociology of Gender and Work collection reflects these main areas of study in gender and work. In addition to undergraduate and graduate syllabi about gender and work, it includes sociology of work syllabi that emphasize gender (see Cindy Anderson, Dana Britton, and Karla Erickson’s syllabi), as well as syllabi that examine more specific areas such as gender and care work (i.e. Cameron Macdonald’s graduate syllabus), and gender and sex work (i.e. Carly Chillmon’s syllabus). Many of the syllabi contain useful information about films, useful websites, and class projects. Some of the films, books, and websites contained in syllabi are listed in the "recommended" sources at the end of this collection for quick reference.